2023
DOI: 10.1007/s00592-023-02167-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of early macular microangiopathy in subjects with prediabetes using optical coherence tomography angiography and fundus photography

Shereen El Sawy,
Mirrette Bekhit,
Alaa Abdelhamid
et al.

Abstract: Aims Early detection of retinal microangiopathy in patients with prediabetes may reduce diabetic retinopathy complications. The aim of this study was to assess early macular vascular changes in prediabetics before development of over diabetes using OCTA and fundus photography. Methods In this cross-sectional study, 66 prediabetic individuals and 66 normal controls underwent clinical, laboratory, and fundus photography evaluation followed by OCTA macular im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
1
Order By: Relevance
“…However, another study reported that the percentage of SCP and DCP vessel density perfusion (VDP) was signi cantly lower in prediabetics compared to the control group (23). In addition, Arias et al revealed that vessel density and perfusion density decreased in prediabetics compared to the control group (24). In our study, we found a statistically signi cant decrease in plexus perfusion density in the temporal quadrant of the SCP and the inferior and temporal quadrants of the DCP.…”
Section: Discussioncontrasting
confidence: 42%
“…However, another study reported that the percentage of SCP and DCP vessel density perfusion (VDP) was signi cantly lower in prediabetics compared to the control group (23). In addition, Arias et al revealed that vessel density and perfusion density decreased in prediabetics compared to the control group (24). In our study, we found a statistically signi cant decrease in plexus perfusion density in the temporal quadrant of the SCP and the inferior and temporal quadrants of the DCP.…”
Section: Discussioncontrasting
confidence: 42%
“…One study looked at a new parameter, microangiopathy, on OCTA. El Sawy et al were able to detect retinal microangiopathy in 36.4% of pre-diabetics, capillary NPA in 53.8%, and the disorganisation of the SCP in 56.8% of pre-diabetic patients, compared to only 10.6% detected in CFP [136].…”
Section: Pre-diabetesmentioning
confidence: 97%